2002
DOI: 10.1111/1475-4983.00276
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomy and stratigraphical significance of the Anglo–Welsh Cryptolithinae (Trinucleidae, Trilobita)

Abstract: ABSTRACT. The taxonomic status of the stratigraphically-important Caradoc genera Salterolithus Bancroft, 1929, Broeggerolithus Lamont, 1935 and Smeathenia Dean, 1960 and the species therein is critically reviewed. The radial alignment patterns of the fringe pits within the E arcs are used to distinguish Salterolithus from Broeggerolithus; fringe morphology and pit counts are used to distinguish species within these genera.`Broeggerolithus' harnagensis is reassigned to Salterolithus and S. praecursor, S. carac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The number of pits per arc refers to half fringe counts (variability currently ranges in ±2 pits). Different authors have documented that this practice does not induce much error despite fringe asymmetries (e.g., Whittington, 1968;Hughes, 1970;Bowdler-Hicks et al, 2002). Pits are counted in In and II; irregularities in distribution prevented objective Pothe, 1995, originally assigned to the former genus, is considered by us to be a subjective synonym of the type species of Hunickenolithus (H. pozoensis).…”
Section: Systematic Paleontologymentioning
confidence: 96%
“…The number of pits per arc refers to half fringe counts (variability currently ranges in ±2 pits). Different authors have documented that this practice does not induce much error despite fringe asymmetries (e.g., Whittington, 1968;Hughes, 1970;Bowdler-Hicks et al, 2002). Pits are counted in In and II; irregularities in distribution prevented objective Pothe, 1995, originally assigned to the former genus, is considered by us to be a subjective synonym of the type species of Hunickenolithus (H. pozoensis).…”
Section: Systematic Paleontologymentioning
confidence: 96%
“…Many trinucleid genera have a limited palaeogeographical distribution, and a high degree of endemicity is typical: Chinese trinucleids (Zhou & Zhen 2008) are mostly different from Bohemian and Moroccan (Havlíček & Vaněk 1966) and Scoto‐Appalachian (Bowdler‐Hicks et al . 2002) faunas. Ordovician microcontinents and terranes were characterized by another suite of endemics, such as in Avalonia (Owen & Ingham (1988) and references therein; see also Kennedy & Stammers 2018), the Central Andean Basin of Gondwana (Hughes & Wright 1970; Přibyl & Vaněk 1980; Waisfeld & Vaccari 2003) and the Precordillera – Cuyania Terrane, Argentina (Baldis & Pöthe de Baldis 1995; Waisfeld & Vaccari 2003).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…However, it is probably not true of such genera as Protolloydolithus or Declivolithus Přibyl & Vaněk, 1967, which had extensive and apparently flattened fringes, and some others with steeply inclined fringes, such as Salterolithus Bancroft, 1929 (Bowdler‐Hicks et al . 2002, pl. 1 fig.…”
Section: Fantasticolithus and Hypotheses Of Trinucleimorph Life Habitsmentioning
confidence: 99%
“…All the shelly fossils used to subdivide the type Caradoc are, however, environmentally controlled facies fossils that appear wherever the palaeoenvironment suited them, and thus biostratigraphic correlations based on them are useless (Hurst, 1979 a ). For example, it is not very encouraging to find that Heterothis alternata (J. de C. Sowerby), the brachiopod dominating the Alternata Limestone Formation, also occurs sporadically in lenses throughout the overlying strata, from basal Cheneyan to topmost Streffordian stages (Harper, 1978); nor that modern taxonomic studies have shown that the important cryptolithinid trilobites, widely used for Caradocian zonation, consist of very variable populations with environmentally constrained morphotypes and species (Owen & Ingham, 1988; Bowdler-Hicks, Ingham & Owen, 2002).…”
Section: Local Geologymentioning
confidence: 99%